Penguatan Peran Ibu dalam Pola Pendampingan Terhadap Anak dan Media Baru - Amala saputri, Nur; Satriadi Nur Arifin, Tommy (Jurnal Ilmiah Padma Sri Kreshna, 2019)
The presence of new media changes major changes in people's lives. Mothers as family educators must have the knowledge and understanding of new media. In order to educate children and families in using new media well. This service activity is intended to provide knowledge about new media, specifically in the pattern of mother to child assistance and the media. The methods used are reflection, lectures, simulations, and discussions about new media. Participants who took part in this activity were PKK Mothers of Demen village aged 25-60 years. The results of this activity include 6 patterns used by mothers in assisting children and the media. The pattern is (1) Mothers must be able to argue and ask for information or content that can be paid by the child. (2) Set the time for children to use new media. (3) Using safe mode when the child is operating a smartphone, specifically for elementary school age children down. (4) Supervise and check the smartphone used by the child. (5) Inviting children to chat and discuss their daily activities after children, while also making family groups on Whatsapp as a family room to chat online. (6) Combine or report deceptive content and content that contains negative SARA issues. PKK Mothers who participated in this activity gave many positive responses and became more understanding in using new media when accompanying the child when using new media.Â